LEGAL PROTECTION FOR THE CONCEPT OF GREEN NOTARY FOR NOTARIAL OFFICERS - Dzakiah, Wanda Putri; Rahayu, Mella Ismelina Farma (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
The growing emphasis on sustainability within the legal sector has given rise to the concept of the green notary, which promotes digitalization and the reduction of paper-based documentation in notarial practices. This study examines the legal protections afforded to Notaries who adopt green notary practices in Indonesia. Employing a normative juridical research method, this study reviews applicable laws, legal doctrines, and scholarly literature, with particular focus on the compatibility of green notary practices with the principles of legal certainty, professional responsibility, and notarial ethics. The findings indicate that although the green notary concept has not yet been expressly regulated, existing legal frameworks—namely the Notary Law, the Electronic Information and Transactions Law, and the Personal Data Protection Law—may serve as an implicit legal basis for its implementation. The application of green notary practices introduces important legal implications relating to the scope of notarial authority, professional accountability, data protection obligations, and ethical conduct. Accordingly, regulatory harmonization, the establishment of detailed operational guidelines, and the formulation of digital professional ethics standards are essential to ensure that green notary practices are legally valid, efficient, and sustainable in the contemporary digital era.